DETERMINATION OF HUMAN DEVELOPMENT INDEX IN PENAJAM PASER UTARA - Saputra, Aksel Ary; Juliannisa, Indri Arrafi (Jurnal Edukasi (Ekonomi, Pendidikan dan Akuntansi), 2025)
Penajam Paser Utara Regency, which has been designated as the location of the Indonesian Capital City (IKN), faces problems in increasing the Human Development Index (HDI). This study aims to determine the influence of health, education, and welfare dimension indicators directly and indirectly on HDI and economic growth. The method used is the "MICMAC" Matrix of Cross Impact Multiplications Applied to a Classification analysis with a sample of 115 respondents aged 15 years and over in Penajam Paser Utara Regency. The results of the analysis group the indicators into four quadrants: (1) Determinant variables include access to health services, health facilities, number of schools, education curriculum, and workforce participation have a direct influence and low dependence on HDI; (2) Relay variables include nutritional status, health information, school fees, school facilities, access to basic services, and income have a high influence and high dependence; (3) Dependent variables include BOS funds and minimum wages, with low influence but high dependence; and (4) Autonomous variables include environmental quality and inflation, with low influence and dependence. Judging from the order of variables, namely nutritional status, access to health services, and health information occupy the three largest variables that have a strong influence directly and indirectly. This finding provides strategic guidance for local governments to prioritize policies that support determinant variables as the main drivers of increasing the HDI in Penajam Paser Utara Regency.